A systematic review of HHV-6 infections in recipients of organ and tissue transplantation and chimeric antigen receptor T-cell infusions - Abad, Cybele Lara R.; Razonable, Raymund R. (Frontiers in Virology, 2025)
BackgroundWe systematically reviewed the published literature to describe the epidemiology and outcomes of human herpes virus 6 (HHV-6) syndromes and diseases after solid organ transplantation (SOT), hematopoietic transplantation (HCT), and chimeric antigen receptor T-cell (CAR-T) therapy.MethodsPubMed, Scopus, Embase, and Ovid/Medline were reviewed from inception through May 31, 2024, using the keywords HHV-6 and transplantation or CAR-T. Abstracts, case reports, and cohort and case–control studies among adults that were published or translated into English were included.ResultsA total of 136 case reports or series contributed 268 unique cases—225 HCT, 37 SOT, and 6 CAR-T—while 39 cohort studies on HCT (28), SOT (9), CAR-T (1), and mixed SOT/HCT (1) recipients were included. The HHV-6 incidence varied widely from 1% to 95% among cohort studies on HCT and SOT but was low in CAR-T recipients (5.6%). Among the case reports, the median age was 46 years (range, 18–73 years), and most were men (159/236, 67.4%). HHV-6 subtyping was performed only in 66 cases, and 46 were variant B. There were 10 cases that were chromosomally integrated (ciHHV-6). Among the 268 cases with detailed clinical information, fever was reported only in 89 patients (33.2%). The most common clinical syndrome was neurological (204/268, 76.1%), followed by viral syndrome (28/268, 10.4%) and disseminated disease (14/268, 5.2%). The initial therapy was ganciclovir (87/234, 37.2%) or foscarnet (82/234, 35%). At least a third of patients developed neurological sequelae (45/151, 29.8%). HHV-6-attributable mortality was 20.6% (22/107).ConclusionsNeurological disease is the most frequent clinical syndrome of HHV-6 infection. Early recognition of limbic involvement either through the triad of confusion, amnesia, and seizures or through compatible MRI findings may help with early identification. Diagnosis is secured through molecular methods, although an extremely high viral load needs to be interpreted in the context of ciHHV-6. The neurological sequelae of HHV-6 can be disabling and cause significant morbidity.